We Cry Justice : Reading the Bible with the Poor People's Campaign. - Theoharis, Liz (Broadleaf Books, 2021)
In We Cry Justice, leaders of the Poor People's Campaign: A National Call for Moral Revival uncover what the Bible really says about justice and poverty. Liz Theoharis is joined by pastors, organizers, scholars, low-wage workers, and people in poverty in interpreting sacred stories about the poor seeking healing, justice, and freedom. Find in the pages of Scripture God's persistent call to repair the breach and fight poverty, not the poor.